KUALITAS MANUSIA MENUJU SATU ABAD GEREJA PROTESTAN MALUKU - Johny Christian Ruhulessin (Pattimura University, 2022)
Church renewal needs that the ministry of the church must influence human beings as subjects of the church. This paper aims to provide thoughts on how the correlation between human quality and service planning for the Protestant Church of Maluku (GPM) approaches the One Century of GPM in 2035. Church service planning becomes quality, relevant and contextual, and can be implemented, only when the church prepares the church's human resources properly and quality. The Protestant Church of Maluku approaching one century needs to continuously improve and evaluate itself adaptively, improve its quality pro-actively, in facing various geographical challenges, environmental challenges as well as trends in social, community, and religious change and development. The dimension of human quality correlates well with service planning, as well as with the challenges and problems faced, but also with the nature of the church as a religious organization. Therefore, it is important to map the problems that are being and will be faced in the approach of a century of planning for GPM services. Mapping this problem must be with the aim of achieving idealism while remaining realistic, as a form of GPM growth mindset, growing in faith. At least GPM must pay attention to issues that may become collective reflection, as part of effective service planning for the human quality of GPM, namely: issues of religious life, improvement of the quality of democracy, arrangement of planning in harmony with strengthening human resources, and three serious challenges church is disruption, ecology, and emotion. Thus GPM reflects on the journey of a century of calling for GPM on the land of Maluku and North Maluku